Permafrost model in coarse-blocky deposits for the Dry Andes, Argentina (28°-33° s) - Tapia Baldis, Carla Cintia; Trombotto, Dario Tomas (Cuadernos de Investigación Geográfica)
In this work, a statistical permafrost distribution model for coarseblocky deposits in the Dry Andes of Argentina (28-33°S) is presented. The empiric mathematical formulation was based on a logistic regression. The final model is a combination of two independent occurrence probability models: a) a mean annual air temperature-terrain ruggedness model and, b) a mean annual air temperaturepotential incoming solar radiation model. For all cases, calibration was made according the complete geomorphological characterization of a periglacial basin with 250 km2. Lately, the results of probabilistic model were extrapolated to the whole study area in the Dry Andes and compared with the Argentine rock glacier inventory data base. High permafrost likelihood, in coarse debris, is expected above 4200 and 5700 m a.s.l., from south to north in the study area and covers a surface of approximately 1200 km2. Medium permafrost likelihood is expected above 3400 and 4200 m a.s.l. with a surface of 6178 km2 while low permafrost likelihood, occurs between 3000 and 3400 m a.s.l. with an area of 11.060 km2. These findings indicate that permafrost may occur in several types of coarseblocky deposits in the Dry Andes, not only restricted to rock glaciers. Thermal properties of the ground in coarse-blocky deposits allow permafrost permanence, even under unfavourable climatic conditions. The performance of the permafrost model was also tested, considering the transition from cold paleoclimate Tardiglacial to present climatic conditions. During the warming, likely permafrost surface reduced from 56 to 13%. In the same way, rock glaciers with high and medium permafrost likelihood decrease from 62 to 30%, respectively while, rock glaciers with low likelihood and no permafrost category, increased 75% and 474%, respectively. Moreover, we identified some sites in which permafrost degradation is arguably expected. About that, 0.9% of the rock glaciers in the study area display possible permafrost degradation and 33% of them, likely permafrost ...